Studi Dramaturgi pada Transpuan Gebby Vesta di Instagram - Andilia, Marcella; Azeharie, Suzy (Koneksi, 2025)
Instagram is an application used by the community to exchange messages and obtain necessary information. The existence of the Instagram social media platform blurs the boundaries between private and public spaces. However, for some individuals, Instagram is utilized to create an image that aligns with their desires. This is related to dramaturgical theory enacted on Instagram, exemplified by an artist and model named Gebby Vesta, who plays a role in this social media theater. In her private Instagram account, Gebby Vesta portrays herself as a beautiful woman often showcasing her body. However, beneath this facade, she is a transwoman. This study aims to examine the dramaturgy that occurs in Gebby Vesta's Instagram presence. Employing a qualitative approach with a case study method, the research utilizes interview data, literature review, and documentation. The findings of this research indicate that on the front stage, Gebby Vesta endeavors to present herself as a good-looking woman with an ideal body. This is evident from several posts that lead to the perception that Gebby Vesta is a cisgender woman. On the back stage, she reveals her identity as a transwoman, concealing this aspect of herself in front of the public, particularly on her private Instagram account. Instagram merupakan sebuah aplikasi yang digunakan masyarakat untuk bertukar pesan dan mendapatkan informasi yang dibutuhkan. Adanya media sosial Instagram membuat tercampurnya ruang pribadi dengan publik, namun bagi sebagian orang menggunakan Instagram untuk membuat citra yang sesuai dengan keinginan penggunanya. Hal ini berhubungan dengan teori dramaturgi yang dilakukan di Instagram, salah satu artis dan model bernama Gebby Vesta yang memainkan perannya dalam media sosial Instagram. Dalam Instagram pribadinya Gebby Vesta berperan sebagai perempuan yang cantik dan sering menunjukan tubuhnya namun dibalik itu dia adalah seorang transpuan. Pada penelitian ini, penulis ingin melihat bagaimana dramaturgi yang terjadi pada transpuan Gebby Vesta di Instagram. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data yang digunakan dalam penelitian ini adalah wawancara, studi pustaka dan dokumentasi. Hasil dalam penelitian ini menunjukan front stage dia berusaha menampilkan dirinya sebagai perempuan yang baik dan cantik mempunyai tubuh yang ideal. Hal ini terlihat dari beberapa unggahan yang menggiring opini bahwa Gebby Vesta merupakan seorang perempuan. Pada bagian back stage dia sebagai seorang transpuan